Seven new Working Documents 3 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Seven new Working DocumentsThe latest batch of Working Documents to emerge from studies conducted for CTA cover the fields of information for natural resource management policies, small scale food processing and market information systems.In the...